(untitled) (Journal of Pakistan Orthopaedic Association, 2023)
Education is the key in the building of society morals, so it help to provide awareness and in the end get the results that society needs. Unfortunately literacy rate of Pakistan is around 60 % that directly tells the story of awareness and the care people getting for their medical problems. Like other problem in our society Bone and soft tissue sarcomas are also neglected part of our medical side, either because of false beliefs of society, lack of education & awareness, lacking facilities of treating these complicated problems.